Allowing learners to choose: self-controlled practice schedules for learning multiple movement matterns - Wu, W. F. W.; Magill, R. A. (Research Quarterly for Exercise and Sport, 2011)
For this study, we investigated the effects of self-controlled practice on learning multiple motor skills. Thirty participants were randomly assigned to self-control or yoked conditions. Participants learned a three-keystroke pattern with three different relative time structures. Those in the self-control group chose one of three relative time structures before each of 90 practice trials; yoked participants were not allowed to choose but were yoked to a self-control participant and followed that individual's sequence of practice trials. Results of the 24-hr serial transfer test revealed the self-control group exhibited significantly lower relative timing error, absolute error, and total error than the yoked group. Findings further support the efficacy of self-controlled learning.